Difficulty Analysis Graduates Of Japanese Language Education Products That Progress as a Translator and Interpreter - Rejeki Dyah Ayu Suci; Silvia Nurhayati (Chi'e: Journal of Japanese Learning and Teaching, 2019)
There are many problems in translation. This study aims to find out what are the difficulties and factors that cause difficulties experienced by alumni of Japanese Language Education program UNNES from the class of 2005 to 2014 who have professions as translators, both interpreters and translators. The data collection method used in this study is the questionnaire method. The questionnaire used was in the form of a closed questionnaire and 1 item was an open questionnaire. Based on the results of this study, it can be concluded that most alumni have difficulties when translating. The difficulties that most translators experience are knowledge in specific fields, types of texts, methods and techniques of translation, understanding inter-paragraph relationships and mastery of vocabulary. Then, the causal factors such as lack of motivation, confidence, provision of knowledge about translation, finding out your own theory without knowing its validity, lack of interaction with native speakers, and lack of language skills.